Annual Report on the Working of State Electricity Boards and Electricity Departments, Power and Energy Division Planning Commission Govt. of India April, 1988 - Planning Commission (Planning Commission, 1988)
An Annual Report on the Working of State Electricity Boards and Electricity Departments is enclosed. This Report is in continuation of similar effort made last year and is based on material supplied by the concerned agencies in connection with the assessment of resources for the Annual Plan 1988-89. The period covered is mainly 1985-86 to 1988-89 and both operational and financial working of the agencies have been treated in the Report.
(Power and Energy Division) Planning Commission Govt of India
(Power and Energy Division) Planning Commission Govt. of India